Enhanced Soil Solarization against Fusarium oxysporum f. sp. lycopersici in the Uplands - Radwan M. Barakat; Mohammad I. AL-Masri (International Journal of Agronomy, 2012)
Soil solarization tests against Fusarium oxysporum f. sp. lycopersici, the causal agent of tomato Fusarium wilt, were conducted for seven weeks through July and August 2008 and 2009 in the climatic conditions of Al-Aroub Agricultural Experimental Station, located in the southern mountains of the West Bank, Palestine. Double polyethylene (DPE) sheets, regular polyethylene (PE) sheets, and virtually impermeable films (VIF) were compared to examine their effects on soil temperature, disease severity, and plant growth. Results showed that in comparison to the control, PE, DPE, and VIF treatments increased the mean maximum soil temperatures by 10.2, 14.1, and 8.8°C, respectively, in 2008 and by 10.2, 12.6, and 8.3°C respectively, in 2009. The longest length of time recorded for temperature above 45°C under DPE sheets were 220 hours in 2008 and 218 hours in 2009. The treatments reduced the pathogen population by 86% and the disease by 43% under the DPE treatment in 2009 and to a lesser extent by the other treatments. Increases of up to 94% in fresh plant weight and up to 60% in plant dry weight were evident under the same treatment. The treatments also increased soil organic matter, both nitrogen forms, and major cations.